PENYULUHAN TENTANG PERJANJIAN MENURUT KITAB UNDANG – UNDANG HUKUM PERDATA - Nurasiah Harahap (Fakultas Hukum universitas Islam Sumatera Utara, 2020)
AbstractThe participants of legal education in Harjosari I Village, Medan Amplas District, Medan City, North Sumatra Province generally do not understand the importance of an agreement made in writing even though according to the provisions of Article 1313 of the Civil Law (KUHPerdata) that consent is an act in which 1 (one ) people or more bind themselves to one or more other people. This means that an agreement can be made in writing and orally as long as it is not prohibited by law, does not conflict with public order and does not conflict with morals. So that a problem arises in the community of Harjosari I Village, the existence of an association of women in the form of an arisan which results in debts between them and they complain to the Harjosari I village head. Therefore, it is deemed necessary to carry out Community Service in the kelurahan under the title